Clinic-based diabetes screening at the time of HIV testing and associations with poor clinical outcomes in South Africa: a cohort study - Rachel W. Kubiak; Mario Kratz; Ayesha A. Motala; Sean Galagan; Sabina Govere; Elisabeth R. Brown; Mahomed-Yunus S. Moosa; Paul K. Drain (BMC Infectious Diseases, 2021)
Abstract Background HIV clinical care programs in high burden settings are uniquely positioned to facilitate diabetes diagnosis, which is a major challenge. However, in sub-Saharan Africa, data on the burden of diabetes among people living with HIV (PLHIV) and its impact on HIV outcomes is sparse. Methods We enrolled adults presenting for HIV testing at an outpatient clinic in Durban. Those who tested positive for HIV-infection were screened for diabetes using a point-of-care hemoglobin A1c (HbA1c) test. We used log-binomial, Poisson, and Cox proportional hazard models adjusting for confounders to estimate the relationship of diabetes (HbA1c ≥ 6.5%) with the outcomes of HIV viral suppression (< 50 copies/mL) 4–8 months after antiretroviral therapy initiation, retention in care, hospitalization, tuberculosis, and death over 12 months. Results Among 1369 PLHIV, 0.5% (n = 7) reported a prior diabetes diagnosis, 20.6% (95% CI 18.5–22.8%, n = 282) screened positive for pre-diabetes (HbA1c 5.7–6.4%) and 3.5% (95% CI 2.7–4.6%, n = 48) for diabetes. The number needed to screen to identify one new PLHIV with diabetes was 46.5 persons overall and 36.5 restricting to those with BMI ≥ 25 kg/m2. Compared to PLHIV without diabetes, the risk of study outcomes among those with diabetes was not statistically significant, although the adjusted hazard of death was 1.79 (95% CI 0.41–7.87). Conclusions Diabetes and pre-diabetes were common among adults testing positive for HIV and associated with death. Clinic-based diabetes screening could be targeted to higher risk groups and may improve HIV treatment outcomes.